2019
DOI: 10.1016/j.jecp.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Motor imagery during action observation enhances automatic imitation in children with and without developmental coordination disorder

Abstract: Developmental coordination disorder (DCD) is a neurodevelopmental disorder characterised by uncoordinated movement relative to age. While action observation (AO) and motor imagery (MI) can both independently enhance movement skills in children, we report the first study to assess the effects of combined action observation and motor imagery (AO+MI) on automatic imitation in children aged 7-12 years, both with (n = 12) and without DCD (n = 12). On each trial participants planned to execute an instructed rhythmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 61 publications
4
55
1
Order By: Relevance
“…In fact, the AO+MI group performed significantly quicker than the control group by the second training block (T2) and maintained this advantage in the subsequent training block (T3) and post-test phase (Figure 3a). These results are the first to demonstrate that AO+MI interventions can aid visuomotor adaptation and support previous research that has shown beneficial effects of AO+MI on performance outcomes generally (Bek et al, 2019;Romano-Smith et al, 2018; and within the DCD population specifically (Scott et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In fact, the AO+MI group performed significantly quicker than the control group by the second training block (T2) and maintained this advantage in the subsequent training block (T3) and post-test phase (Figure 3a). These results are the first to demonstrate that AO+MI interventions can aid visuomotor adaptation and support previous research that has shown beneficial effects of AO+MI on performance outcomes generally (Bek et al, 2019;Romano-Smith et al, 2018; and within the DCD population specifically (Scott et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…Control. Participants in the control group (seven male, three female; age M = 9.0, SD = 1.41 years) watched 42 second clips of a nature documentary that contained no human motor content (Scott et al, 2019) followed by an immediate physical practice trial. The duration of video clips was chosen in order to represent a total viewing time that was equivalent to the total duration of the AO+MI videos.…”
Section: Intervention Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest that combining or simultaneously using AO and MI has a better effect on exercise outcomes than MI or AO alone (Eaves et al, 2016). It has also been verified that MI and AO are more effective than MI alone in interventions for children (Scott et al, 2019). It is also reported that MI intervention causes a temporary deterioration in motor performance due to mental fatigue caused by repeated MI (Rozand et al, 2016).…”
Section: Discussion (Neurorehabilitation Study)mentioning
confidence: 99%
“…That is, in line with the model, the combined use of motor imagery and action observation was a more effective tool for impacting motor skills in children with varying motor abilities compared with motor imagery and action observation in isolation. Recent work by Scott et al 22 and Marshall et al 23 provided further empirical support for the improved efficacy of the combined use of motor imagery and action observation over and above the isolated use of either motor imagery or action observation. Marshallet al, 23 for example, tested the combined use of motor imagery and action observation to examine its effect on the kinematics of eye–hand coordination during a visuomotor rotation task.…”
Section: The Use Of Motor Imagery and Action Observation For Remediatmentioning
confidence: 97%